Superficial nephrons in BALB/c and C57BL/6 mice facilitate in vivo multiphoton microscopy of the kidney. - Ina Maria Schießl; Sophia Bardehle; Hayo Castrop (PLoS ONE, 2013)
Multiphoton microscopy (MPM) offers a unique approach for addressing both the function and structure of an organ in near-real time in the live animal. The method however is limited by the tissue-specific penetration depth of the excitation laser. In the kidney, structures in the range of 100 µm from the surface are accessible for MPM. This limitation of MPM aggravates the investigation of the function of structures located deeper in the renal cortex, like the glomerulus and the juxtaglomerular apparatus. In view of the relevance of gene-targeted mice for investigating the function of these structures, we aimed to identify a mouse strain with a high percentage of superficially located glomeruli. The mean distance of the 30 most superficial glomeruli from the kidney surface was determined in 10 commonly used mouse strains. The mean depth of glomeruli was 118.4±3.4, 123.0±2.7, 133.7±3.0, 132.3±2.6, 141.0±4.0, 145.3±4.3, 148.9±4.2, 151.6±2.7, 167.7±3.9, and 207.8±3.2 µm in kidney sections from 4-week-old C3H/HeN, BALB/cAnN, SJL/J, C57BL/6N, DBA/2N, CD1 (CRI), 129S2/SvPas, CB6F1, FVB/N and NMRI (Han) mice, respectively (n = 5 animals from each strain). The mean distance from the kidney surface of the most superficial glomeruli was significantly lower in the strains C3H/HeN Crl, BALB/cAnN, DBA/2NCrl, and C57BL/6N when compared to a peer group consisting of all the other strains (p<.0001). In 10-week-old mice, the most superficial glomeruli were located deeper in the cortex when compared to 4-week-old animals, with BALB/cAnN and C57BL/6N being the strains with the highest percentage of superficial glomeruli (25% percentile 116.7 and 121.9 µm, respectively). In summary, due to significantly more superficial glomeruli compared to other commonly used strains, BALB/cAnN and C57BL/6N mice appear to be particularly suitable for the investigation of glomerular function using MPM.